Physical overstrain in sports: modern prevention and rehabilitation procedure - Lutkov, V. F.; Miller, L. L.; Smirnov, G. I.; Shadrin, D. I. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze exposures to the microtraumatic disease risks and benefits of Traumel-C for treatment of the microtraumatic-disease-associated impaired local circulation in gorodki players, to facilitate trainings and special fitness improvement efforts.